2017
DOI: 10.1590/2359-3997000000265
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in youth and sleep quality: is there a link?

Abstract: The present study suggests a link between overweight/obesity and altered sleep quality due to compromised non-rapid eye movement sleep, an indirect marker of sleep quality. There was also a link between slow-wave sleep duration and insulin resistance. We must find a strategy to provide adequate slow-wave sleep duration to reduce the obesity epidemic at young ages. Further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
1
18
2
1
Order By: Relevance
“…One possible explanation is that prolonged sleep duration reflects compensation for poor-quality and/or interrupted sleep, which may be more common among overweight and obese person. A study showed that, compared with normal-weight children, overweight and obese children had less slow-wave sleep (SWS), which plays a major role in body restorative processes and energy metabolism [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that prolonged sleep duration reflects compensation for poor-quality and/or interrupted sleep, which may be more common among overweight and obese person. A study showed that, compared with normal-weight children, overweight and obese children had less slow-wave sleep (SWS), which plays a major role in body restorative processes and energy metabolism [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from obesity, overweight could also be a risk factor for negative health consequence [ 13 ]; however, few studies have mentioned the effect of short sleep on overweight risk. A link between no-rapid eye movement sleep and overweight was suggested, but the research has a relatively small sample size [ 14 ]. Moreover, child overweight, as the intermediate state between normal weight and obesity, could be reversed, which means it is worthy of exploration as an independent negative outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Most national and international guidelines focus on recommendations for sleep duration, since prior research has demonstrated that insufficient sleep duration during adolescence is associated with a variety of cognitive, psychological, and health risks, including higher body mass index (BMI) [810], greater body fat [11], and increased insulin resistance [12]. However, emerging evidence suggests that sleep quality [1315] and timing may also affect adolescent cardiometabolic risk factors [7]. For instance, later bedtimes are associated with greater BMI [10, 16], body fat [11] and higher systolic blood pressure in children and adolescents [17].…”
Section: Introductionmentioning
confidence: 99%